Ranking Cloud Computing Criteria in Developing Electronic Communications Services Using MCDM - Eslami Mahdiabadi, Saeid (2021)
The main purpose of this study was ranking cloud computing criteria in developing electronic communications services using multiple-criteria decision analysis methodology (MCDM). This correlational research was applied in terms of purpose. Statistical population of the study included ICT experts of the steel industry in Yazd province (industrial experts), among which, 312 individuals were selected using purposeful nonprobability (judgmental) sampling method. Considering the conducted investigations and critically reviewing the related books and articles, the variables, criteria, and scales were identified using cloud computing technology. To analyze the data, MCDM and fuzzy logic calculations were utilized in Expert Choice software. According to the results and considering fuzzy calculations related to the capabilities of cloud computing in developing electronic communications services, the most important criteria in the "IT management in steel industries" cluster having (A) network code was "communicating with steel industries` costumers" having (AB) network code and fuzzy network weight equal to 0.096; the most important criteria in "cloud computing capabilities" cluster having (B) network code were "reducing steel industries` costs" having (BA) network code and fuzzy network weight equal to 0.191; and "providing rapid services to steel industries` costumers" having (BB) network code and fuzzy network weight equal to 0.120. on the other hand, the most important criteria in "developing electronic communications services" cluster having (C) network code was "storing the data in electronic communications services" having (CD) network code and fuzzy network weight equal to 0.123, since based on fuzzy logic calculation, they had the highest fuzzy rank in Matlab programming environment regarding cloud computing capabilities in developing electronic communications services.